The Study Of Conversion Cpo To Polyol (Polyalcohol) - F. S. Budi; z. Abidin (Dept. of Chemical Engineering, Diponegoro University, 2007)
Indonesia is the second big CPO producer after Malaysia. The CPO production of Indonesia gradually increases and reaches 8.2 million tones. About two third of it is used to meet the domestic will receive little income. Therefore, it must be converted into the other product, which has the high value. The main component of it is glyceride composed of glycerol and fatty acid. The glyceride can be converted into polyol (polyalcohol) which is the material in manufacturing polyurethane, cosmetic, lubricant etc. the process of converting of CPO into polyol is called the hydroxylation. This research aim to study the hydroxylation process of CPO into polyol and to optimize the variable which really affect the hydroxyl number of product. Based on the experiment, the optimum condition of hydroxylation of CPO with the hydrogen peroxide (H2O2) and the formic acid (HCOOH) into polyol is got as follows: temperature 50 0C, composition of reactan 40% and time 2 hours. The polyol produced has the hydroxyl number 148.Keywords : CPO, hydroxylation, polyol